San Francisco March for Peace in Central America and Equality in South Africa - Watkins, Howard::::::::: (1987)
Fresnans and others in front of Fresno banner; on left: Belinda Guerrero holding FSLM flag; middle: Christine Watkins holding stroller with Robin Watkins; Karrin Wommack in bluish-purple print; Sara Hedgepeth Harris on right of Women's International League for Peace and Freedom banner; far right: John Palofox, Luis Jovel holding cardboard box and Al Robles "Fresno Wants Peace in Central America + Equality in South Africa"